Customer relationship management (CRM) in life insurance sector: An empirical study of Bao Viet Life Corporation - Nguyen Thu Trang (H. : ĐHQGHN, 2020)
The research has highlighted that Bao Viet Life has taken a rather narrow view of customer relationship management (CRM) and as such, benefits have been limited. Hence, for majority of life insurance companies, including Bao Viet Life, there should be a comprehensive CRM plan which is based on company's current state to guide and improve it.